UTILIZING PEER AND TEACHER FEEDBACK IN ACADEMIC WRITING CLASS - Taufiqulloh Yuvita Imam Yuliarto (University of Kuningan, 2016)
A process approach is usually employed in the classroom instruction of academic writing, particulary essay writing, in the Indonesian colleges or universities. This study investigates the role of teacher and peer feedback inserted in the steps of writing process on studentsâ€™ writing achievement. It is an experimental research conducted at the English Education Department of Pancasakti University Tegal Central Java Indonesia, in the seven semester of theÂ academic year 2015/2016. The participants of this study are 40 students who attended essay writing class. The instrument is essay writing test which was administered before and after treatment to both experimental and control group. By using paired-sample t-test and f-test, it was found that the use of teacher and peer feedback were effective to teach essay writing. Such a technique contributed a significant improvemental to the students writing achievement in the experimental group. The result also showed that the writing achievement of the students in the experimental group was better than that of those in the control group. To conclude,Â utilizing teacher and peer feedback is considered to be one of the effective ways for the students in learning essay writing. However, some drawbacks were found that need to be taken into account in the next related researches.Keywords: Teacher feedback, peer feedback, essay writing